3D Synthetic Peptide-based Architectures for the Engineering of the Enteric Nervous System - Brun, Paola (Sci Rep, 2019)
Damage of enteric neurons and partial or total loss of selective neuronal populations are reported in intestinal disorders including inflammatory bowel diseases and necrotizing enterocolitis. To develop three-dimensional scaffolds for enteric neurons we propose the decoration of ionic-complementary self-assembling peptide (SAP) hydrogels, namely EAK or EAbuK, with bioactive motives. Our results showed the ability of EAK in supporting neuronal cell attachment and neurite development. Therefore, EAK was covalently conjugated to: RGD, (GRGDSP)(4)K (fibronectin), FRHRNRKGY (h-vitronectin, named HVP), IKVAV (laminin), and type 1 Insulin-like Growth Factor (IGF-1). Chemoselective ligation was applied for the SAP conjugation with IGF-1 and the other longer sequences. Freshly isolated murine enteric neurons attached and grew on all functionalized EAK but IGF-1. Cell-cell contact was evident on hydrogels enriched with (GRGDSP)(4)K and HVP. Moreover (GRGDSP)(4)K significantly increased mRNA expression of neurotrophin-3 and nerve growth factor, two trophic factors supporting neuronal survival and differentiation, whereas IKVAV decoration specifically increased mRNA expression of acetylcholinesterase and choline acetyltransferase, genes involved in synaptic communication between cholinergic neurons. Thus, decorated hydrogels are proposed as injectable scaffolds to support in loco survival of enteric neurons, foster synaptic communication, or drive the differentiation of neuronal subtypes.